PEMBUATAN DAN UJI MUTU FISIK SEDIAAN PASTA GIGI ESKTRAK DAUN BIDARA ARAB (Ziziphus spina-christi L.) ASAL KABUPATEN GOWA - Muhammad Alfajri Samsuddin; Hamka, Zulfahmi (Akademi Farmasi Yamasi Makassar, 2024)
Abstract. Toothpaste is one of the preparations that can be used in maintaining dental hygiene. Toothpaste can be made from natural ingredients, one of which is from the Arabian Bidara plant which has antibacterial properties. This study aims to make and test the physical quality of toothpaste preparations from bidara arabic leaf extract (Ziziphus Spina-Christi L.) with concentrations of 4% and 5%. Physical quality tests carried out include: Organoleptic test, homogeneity test, pH test and spreadability test. The results of this study state that the extract of Arabian Bidara leaves (Ziziphus Spina-Christi L.) can be made toothpaste preparations with concentrations of 4% and 5% which meet the requirements of the physical quality test of toothpaste preparations.